Towards the total synthesis of hypoestoxide and dihypoestoxide - Cousin, Peggy (2017)
The involvement of hetero Diels-Alder dimerisations in the biosynthesis of natural products has been a source of debate for many years. Hypoestoxide and dihypoestoxide are two verticillane-type diterpenoids with closely related structures. Both were isolated from the same extracts of Hypoestes rosea in Nigeria. These two natural products constitute another example of a potential hetero Diels-Alder dimerisation in biosynthesis. Therefore, this thesis reports the work towards the diterpene hypoestoxide in order to study the hetero Diels-Alder dimerisation.